2018
DOI: 10.1200/jco.2017.76.3425
|View full text |Cite
|
Sign up to set email alerts
|

Measurable Residual Disease at Induction Redefines Partial Response in Acute Myeloid Leukemia and Stratifies Outcomes in Patients at Standard Risk Without NPM1 Mutations

Abstract: We investigated the effect on outcome of measurable or minimal residual disease (MRD) status after each induction course to evaluate the extent of its predictive value for acute myeloid leukemia (AML) risk groups, including NPM1 wild-type (wt) standard risk, when incorporated with other induction response criteria. MethodsAs part of the NCRI AML17 trial, 2,450 younger adult patients with AML or high-risk myelodysplastic syndrome had prospective multiparameter flow cytometric MRD (MFC-MRD) assessment. After cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 36 publications
6
162
0
Order By: Relevance
“…While the relapse for such patients is not 100%, it does appear to approach 60%, although as will be explained, it may be possible to reduce the impact of pre-transplant MRD. Similar findings about the impact of MFC detection of MRD has been published by others, including a recent report from Freeman et al concerning the British AML-17 trial [13]. In their study, they found that presence of MFC-detected MRD was highly predictive of overall survival, and that allogeneic transplant benefit was more apparent in MRD+ than in MRD− patients.…”
Section: Impact Of Mrd By Disease Categorysupporting
confidence: 85%
“…While the relapse for such patients is not 100%, it does appear to approach 60%, although as will be explained, it may be possible to reduce the impact of pre-transplant MRD. Similar findings about the impact of MFC detection of MRD has been published by others, including a recent report from Freeman et al concerning the British AML-17 trial [13]. In their study, they found that presence of MFC-detected MRD was highly predictive of overall survival, and that allogeneic transplant benefit was more apparent in MRD+ than in MRD− patients.…”
Section: Impact Of Mrd By Disease Categorysupporting
confidence: 85%
“…Outcome data from multiple previous studies applying MFC to measure residual disease in morphological CR (Schuurhuis et al , ) have contributed to the European LeukaemiaNet (ELN) recommendation that morphological CR without measurable residual disease (CR mrd ‐) be included as a defined response endpoint for AML (Dohner et al , ). CR mrd ‐ by MFC is associated with a significantly better overall survival in younger adults than morphological CR/CR with incomplete blood count recovery (CRi) even after first induction (63% vs. 52% at 5 years) (Freeman et al , ) as previously shown for older patients treated intensively (Freeman et al , ).…”
Section: Outcomes By Mrd Status Of Patients Not In Cr After First Indmentioning
confidence: 74%
“…This prompted us to examine the data for discrepant response assessment by standard criteria and flow cytometric MRD results post‐first induction in the three adult AML trials for which outcomes by MFC MRD status in CR have previously reported by the Dutch‐Belgian Haemato‐Oncology Cooperative Group (HOVON) (Terwijn et al , ) and UK National Cancer Research Institute (NCRI) (Freeman et al , , ) trial groups (Table ). MFC MRD samples were more likely to be haemodilute than morphological samples as not prioritised for ‘first pull’ BM.…”
Section: Outcomes By Mrd Status Of Patients Not In Cr After First Indmentioning
confidence: 99%
“…In case of MRD positivity in BM with negativity in PB at the end of cytoreductive treatment, MRD should be monitored every month for at least 3 months . There is some evidence to suggest that MRD‐positive patients actually may benefit from allo‐HSCT . Conversely, for patients in the intermediate genetic risk group (e.g., concurrent FLT3 ‐ITD), MRD negativity may reduce the likelihood to proceed to transplantation, particularly when other circumstances would argue against allo‐HSCT (e.g., comorbidities).…”
Section: Mrd As Tool To Guide Personalized Treatment In Npm1‐mutated mentioning
confidence: 99%
“…After cytoreductive therapy Detectable mutant NPM1 transcripts in BM or PB after two courses of therapy carry a considerable risk of relapse with inferior survival (26,(47)(48)(49)(50)(51)(52). In one study, as many as 82% of MRD-positive patients in PB relapsed compared to 30% of MRDnegative patients (47).…”
Section: Prognostic Impact Of Mrd In Npm1-mutated Leukemiasmentioning
confidence: 99%